2015 International Siberian Conference on Control and Communications (SIBCON) 2015
DOI: 10.1109/sibcon.2015.7147227
|View full text |Cite
|
Sign up to set email alerts
|

Pulse decomposition in the turn of meander line as a new concept of protection against UWB pulses

Abstract: Pulse decomposition in the turn of a meander line with the homogeneous dielectric filling is analyzed in detail. The study shows that the ultrashort pulse in the turn of a line with strong half-turn coupling is decomposed to subsequent pulses, having levels of 60, 60, -40, 20, -10%, when compared with a signal in the beginning of the turn. We obtained the conditions, providing decomposition of an ultrashort pulse into subsequent pulses. The research reveals the optimum value of capacitive coupling coefficient,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 4 publications
(4 reference statements)
0
4
0
4
Order By: Relevance
“…(The way to illuminate its effect on the signal front is shown [7].) Detailed analysis of the influence of the near-end crosstalk on the waveform in the turn of the air meander line is shown in [5]. It was found that if the delay in the line more than the sum of front, flat top and fall durations, the pulse can pass without distortions (1):…”
Section: Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…(The way to illuminate its effect on the signal front is shown [7].) Detailed analysis of the influence of the near-end crosstalk on the waveform in the turn of the air meander line is shown in [5]. It was found that if the delay in the line more than the sum of front, flat top and fall durations, the pulse can pass without distortions (1):…”
Section: Simulationmentioning
confidence: 99%
“…All-passing properties of the meander line turn are stated in the classic paper [4]. Use of meander distortions enhanced with the increase of the length of the turns and the meander half-turns coupling, even in the homogeneous dielectric filling, is shown [5]. Thus, pulse decomposition in the turn of a meander line with the homogeneous dielectric filling is analyzed in detail, and condition of UWB decomposition into a sequence of pulses with amplitudes not exceeding 60% of the level at the beginning of a turn is presented.…”
Section: Introductionmentioning
confidence: 99%
“…Кроме того, большинство исследований проведено в частотной области, тогда как временной уделено меньше внимания. Между тем изучение процессов во временной области позволит усовершенствовать защиту от сверхкоротких импульсов (СКИ) [3,4]. Актуальны выявление и локализация максимумов сигнала в связанных линиях, поскольку результаты могут быть полезны для выявления и локализации мест возможных паразитных взаимовлияний, излучений и восприимчивости, чтобы своевременно принять меры по их устранению для обеспечения электромагнитной совместимости (ЭМС) и информационной безопасности.…”
unclassified
“…1). При такой длине выбранный в качестве воздействия СКИ в форме трапеции амплитудой 1 В, с длительностью фронта, вершины и спада по 0,1 нс полностью разлагается на два импульса [3].…”
unclassified
“…В этой связи примечателен подход к защите РЭА, основанный на использовании искажений в витке меандровой линии задержки [2][3][4], часто называемом С-секцией [5][6][7]. Достоинством подхода является то, что его реализация может не требовать устройства защиты как такового.…”
unclassified